The Bottlenose Dolphin Epigenetic Aging Tool (BEAT): A Molecular Age Estimation Tool for Small Cetaceans - Beal, Andria P.; Kiszka, Jeremy J.; Wells, Randall S.; Eirin-Lopez, Jose M. (Frontiers in Marine Science, 2019)
Age constitutes a critical parameter for the study of animal populations, providing information about development, environmental effects, survival, and reproduction. Unfortunately, age estimation is not only challenging in large, mobile and legally protected species, but often involves invasive sampling methods. The present work investigates the association between epigenetic modifications and chronological age in small cetaceans. For that purpose, the present study characterized DNA methylation at age-linked genes in an extensively studied, long-term resident common bottlenose dolphin (Tursiops truncatus) community from Sarasota Bay (Florida, USA) for which sampled individuals have a known age. Results led to the identification of two CpG sites that are significantly correlated to dolphin chronological age. Additionally, sex-specific models revealed the potential modulation of such correlation. These findings allowed to develop and validate the “Bottlenose dolphin Epigenetic Age estimation Tool” (BEAT), improving minimally-invasive age estimation in free-ranging small cetaceans. Overall, the BEAT proved to be accurate in estimating age in these organisms. Given its minimally-invasive nature and potential large-scale implementation using skin biopsy samples, this tool can be used to generate age data from free-ranging small cetacean populations.